Climate change adaptation, gender, and mainstreaming: The role of gender in Fiji's relocation initiative - Bertana, Amanda; Blanton, Natalie (Climate and Development, 2022)
Climate change has elucidated already existing gender inequalities associated with unequal access to resources, decision-making processes, and higher exposure to environmental shocks and stressors. Growing acknowledgment of the gender-differentiated implications of climate change in recent years has placed gender equality as a focal point in international discourses on climate change adaptation. The policy perspective of gender equality is universalized, but how it transcribes in local climate change adaptation projects remains elusive. Using the relocation of Vunidogoloa, Fiji, this article explores the tension and compatibility between the way gender equality is discussed and how it is implemented in climate change adaptation projects. © 2022 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; 2010-2019; changements climatiques; discipline; environnement; ethnographie; fidji; océanie; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; sécurité alimentaire; thématiques

Coronavirus, domestic labour and care: Gendered roles locked down - Craig, Lyn (Journal of Sociology, 2020)
The Covid-19 pandemic turned daily lives upside down. Lockdowns and physical distancing meant hundreds of thousands of people switched to working from home, significantly blurring the temporal and spatial boundaries between paid work, domestic labour and caring for others. This article explores gender relations, and the division of employment, domestic labour and care, drawing on early results from an online survey, Work and Care in the Time of Covid-19, carried out between 7 May and 4 June 2020.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; australie; care; covid-19; discipline; division sexuelle du travail; océanie; pandémie; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; sociologie; soins aux enfants; thématiques; travail; travail de reproduction; travail invisible

"I’m strong within myself": Gender, class and emotional capital in childcare - Andrew, Yarrow (British Journal of Sociology of Education, 2015)
Emotions have received increasing attention in educational circles in the last decade. Drawing on Bourdieu, feminist scholars use emotional capital to illustrate the ways gendered inequalities can compound the disadvantages of social class. This paper examines relationships within childcare services in Australia, showing how emotional capital functions as a resource for staff. Data from interviews with childcare staff illustrate key aspects of emotional capital, such as reflexivity, resilience and embodiment. Findings show that investing in emotional capital is the key to a long-lasting commitment to childcare work, and should be valued accordingly. © 2013 Taylor & Francis.
Keywords: 2000 à aujourd'hui; 2010-2019; australie; capital émotionnel; care; discipline; maternité; océanie; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; service de garde; sociologie; thématiques; travail; travail du care

Whose `Special Treatment'? Heterosexism and the Problems with Liberalism - Brickell, Chris (Sexualities, 2001)
This article examines the circulation of heterosexist positions within several recent New Zealand media texts. It argues that a recent form of discourse engages liberal language and assumptions in ways that support the privileged position of heterosexuality and the marginalization of homosexuality. The examples given highlight not only the tenor of some recent representations of homosexuality, but also some problems within liberalism. Most notable of these are liberalism's individualism and its failure to recognize the systemic nature of hierarchical power relationships and the constituting of lesbian and gay subjectivities within these relationships. These problems allow liberalism to play an active part in processes of domination and subordination.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; discours médiatique; histoire; hétérosexisme; libéralisme; nouvelle-zélande; océanie; premier cycle; périodes historiques; rapports de domination; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences